Turkey : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Turkey during the 1990s. Economic activity continued to increase rapidly in 1996, with gross national product growing by 8 percent in real terms, for the second year in a row. Although the pace of activity seemed to ease a little during the first three quarters of the year, production gained momentum in the last quarter, especially in agriculture. The industrial sector continued to expand fastest (7.1 percent), but the service (6.6 percent) and the agricultural sectors (5.2 percent) also performed strongly.